Development, Sexual Cultural Practices and HIV/AIDS in Africa - Page, Samantha (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This open access book introduces the theoretical frameworks and academic debates concerning sexual cultural practices and HIV/AIDS in Africa. It shows how these frameworks have been applied in a practical sense in Africa to investigate sexual cultural practices and their link with HIV/AIDS. The author provides an overview of both the field of study and the methods used during fieldwork. Finally, it assesses the implications of the findings for the conceptualization and provision of current and future HIV/AIDS policies and programs in Africa. This monograph will appeal to policy makers and practitioners working in the field of HIV/AIDS in the Global South as well as academics and students. Samantha Page is Associate Professor of International Development Studies, Department of Global Development and Planning, University of Adger, Norway.